Feeding behavior of a crab according to cheliped number - De Oliveira, Diogo Nunes [UNESP]; Christofoletti, Ronaldo Adriano; Barreto, Egydio Rodrigo [UNESP] (Public Library of Science (PLoS), 2015)
Cheliped loss through autotomy is a common reflexive response in decapod crustaceans. Cheliped loss has direct and indirect effects on feeding behavior which can affect population dynamics and the role of species in the community. In this study, we assessed the impact of autotomy (0, 1, or 2 cheliped loss) on feeding behavior in the crab Pachygrapsus transversus, an omnivorous and abundant species that inhabits subtropical intertidal rocky shores along the South Atlantic Ocean. Autotomy altered crab feeding patterns and foraging behavior; however, the time spent foraging on animal prey or algae was not affected. These results indicate a plasticity of feeding behavior in P. transversus, allowing them to maintain feeding when injured.